PEMBUKTIAN DALAM SENGKETA TATA USAHA NEGARA - Johansyah, Johansyah (Faculty of Law, University of Palembang, 2019)
The purpose of this study is to find out and analyze the evidentiary process at the trial in a State Administration dispute involving evidence, the burden of proof and evaluation of the evidence carried out in the State Administrative Court. This type of research is normative legal research. Proof is a procedure for establishing evidence of a fact in a State Administration case to be used as a basis for consideration in passing a decision. In general explanation of Law Number. 5 of 1986 stated that the teaching of proof used in the State Administrative Court is the teaching of free proof, in the State Administrative Court, the judge plays a more active role in the trial process to obtain material truth. An administrative suit does not in essence delay the implementation of the disputed State Administration Decree. The judge has the authority to provide an assessment of the results of evidence in examining, deciding, and resolving State Administration Disputes based on Article 107 of Law Number 5 of 1986.